Approved and novel strategies in diagnostics of rat bite fever and other Streptobacillus infections in humans and animals. Issue 6 (17th August 2016) - Eisenberg, Tobias; Ewers, Christa; Rau, Jörg; Akimkin, Valerij; Nicklas, Werner
ABSTRACT: Rat bite fever (RBF), a worldwide occurring and most likely under-diagnosed zoonosis caused by Streptobacillus moniliformis, represents the most prominent disease of Streptobacillus infections. Recently, novel members have been described, from which a reservoir in rats and other animal species and a zoonotic potential can be assumed. Despite regularly published case reports, diagnostics of RBF continues to represent a 'diagnostic dilemma', because the mostly applied 16S rRNA sequence analysis may be uncertain for proper pathogen identification. Virtually nothing is known regarding prevalence in humans and animal reservoirs. For a realistic assessment of the pathogen's spread, epidemiology and virulence traits, future studies should focus on the genomic background of Streptobacillus . Full genome sequence analyses of a representative collection of strains might facilitate to unequivocally identify and type isolates. Prevalence studies using selective enrichment mechanisms may also enable the isolation of novel strains and candidate species of this neglected group of microorganisms.